(untitled) (Research, Society and Development, 2020)
The world population has undergone a substantial increase in the last decades and one of the consequences is the increase in the rate of soil waterproofing, which can, as a consequence, bring serious problems such as floods and floods. To avoid these events it is necessary to have an efficient rainwater drainage system, which can be achieved by knowing the probable volume / flow due to a high intensity precipitation event. This research seeks to determine the degree of soil waterproofing in urban basins in the city of Campina Grande - PB via geotechnology. The results showed that for the central areas the degree of waterproofing already reaches values close to 80% and in the peripheral basins this index tends to increase, since it is for these basins that the new housing complexes are being implemented.